The Guided Imagery Therapy Activity "Inner Dialogue-Child Adult Meeting" (ID-CAM): Steps and Applications. Issue 3 (3rd July 2019) - Androutsopoulou, Athena; Viou, Maria
ABSTRACT: The guided imagery therapy activity Inner Dialogue-Child Adult Meeting (ID-CAM) is designed to monitor inner child and adult parts or voices, and the quality of dialogue between them in an imaginary meeting. Dialogical Self Theory constitutes its theoretical background. In analyzing the material generated from this activity, emphasis is placed in the various "meeting resolutions" ("dialogue outcomes"): connection, disconnection, and forced connection between child and adult self. Case examples illustrate steps and applications to help therapists and clients: (a) deal with impasses; (b) understand the depth of current difficulties; (c) rethink case information and possible unsaid trauma; and (d) assess therapy progress. Additional therapy applications are discussed in connection to Dialogical Self Theory. The activity can be used in individual, group, and couples therapy by therapists interested in dialogic perspectives.